Integrated medical and nursing ward rounds in a case of severe pneumonia (医护一体化护理查房在1例重症肺炎患者中的应用) - LI Ying (李影); TANG Ling (唐玲); E Haiyan (鄂海燕); LI Ye (李野); SUN Lei (孙磊); HOU Pengxiao (候朋晓); ZHANG Chunyan (张春艳); REN Yaxing (任亚星); WANG Jin (王晶); FENG Yajing (冯亚静); ZHOU Jie (周洁); HAN Jianping (韩建萍) (中西医结合护理)
This paper summarized the practice of integrated medical and nursing ward rounds for a case of severe pneumonia. An integrated ward rounds team was set up to determine key issues of nursing based on the prognosis, clinical lab examination and symptoms diagnosis. Targeted nursing interventions were carried out to reduce the risk of complications and improve the recovery of the patient. (本文总结1例重症肺炎患者进行医护一体化护理查房经验。由护理部组织建立医护一体化查房小组, 各专科学组就患者疾病转归、化验指标以及临床症状提出护理要点, 针对性实施护理措施, 以降低患者并发症风险, 促进早日康复。)